Conflict management strategy: building harmony in a dynamic work environment - Paroli Paroli (Jurnal Info Sains : Informatika dan Sains, 2024)
A work environment that continues to change and develop gives rise to various conflicts, both between individuals and between organizational units. Therefore, the role of conflict management in dealing with conflict is crucial to ensure balance and productivity in the workplace. This research aims to investigate how strategies can be applied to build harmony in a dynamic work environment. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of conflict management strategies, such as interpersonal skills training, preventive policies, and mediation mechanisms, has a positive impact in creating harmony in a dynamic work environment. Employees and managers who have received conflict management training demonstrate increased ability to manage conflict, which contributes to increased productivity and team well-being. In addition, preventive policies and transparency in decision making help identify and resolve potential conflicts before they escalate, creating an environment that is proactive in dealing with conflict dynamics. These results confirm that a holistic approach to conflict management can have a positive impact on the entire organization, forming a work culture that is balanced between dynamics and harmony.